Investigating rehabilitation by activities involving the trunk to improve balance and gait control in young children with cerebral palsy: A randomized open-label crossover trial protocol - Stella Zografou; Jonathan Pierret; Rajul Vasa; Jean Paysant; Christian Beyaert (PLoS ONE, 2026)
Introduction Children with cerebral palsy (CP) have gross motor and balance disorders altering standing, walking and activities. Since trunk control is central for balance, rehabilitation targeting the trunk is developing. In children with CP aged 5–12 years, rehabilitation by activities involving the trunk (RAIT) based on activities in intermediate postures for 3 months has been demonstrated to significantly improve trunk control while standing and early trunk deceleration and coupled negative ankle power due to plantar flexors while walking autonomously. As motor disorders develop early, the effects of RAIT are investigated in younger children and for longer time: the adapted design of this study is presented. Initial motor disorders in children with CP aged 18 months to 5 years and 6 months are expected to show at least a 30% reduction after RAIT compared to UR (based on prior findings in older children), with progressive improvements of 40% and 50% at 6 and 12 months, respectively, reflecting cumulative training effects. Methods The studied motor disorders include −1- during gait, excessive early anterior deceleration of the sternum (primary outcome) measured by inertial measurement unit, excessive anterior location of center of pressure on affected leg(s), Enhanced Gait Variability Index and step width measured by a walkway equipped with pressure sensors, −2- Altered gross motor, balance and trunk function measured by the item set version of the Gross Motor Function Measurement 66 and by the Early Clinical Assessment of Balance. Expected results All these variables would be influenced by trunk balance and control, and therefore reduced after RAIT. Trial registration ClinicalTrials.gov: NCT06438432 .